Ilya Repin and Kharkiv University - Вовк, Ольга (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2017)
The paper deals with unexplored aspect of Ilya Repin’s biography (1844–1930), the famous artist of our country, namely his connection with corporation of Kharkiv University. Creative, business, personal contacts between artist and graduates, professors, Honorary Members of Kharkiv University were described. University personalities’ contribution to the study of Ilya Repin’s life and creative heritage, remembrance work were also analyzed in the present research.